Monitoring surface water pollution in Algeria using database indices - Ouahiba Bouchama; Lounes Amar (Soil and Water Research)
This study investigated how remote sensing techniques can pinpoint pollution in surface water areas. Researchers focused on the municipalities of Boumerdes, Corso, and Tidjalabine in Algeria's Boumerdes province. The team used geographic information systems (GIS) to analyse pollution levels and their spatial distribution. Specifically, they employed the Normalised Difference Vegetation Index (NDVI) to identify areas teeming with biodiversity and healthy vegetation. Furthermore, the compactness index provided insights into the overall evolution of the drainage network. This data proved invaluable in identifying areas likely impacted by pollution. Our study is part of a scientific approach to detecting, monitoring, and intervening in water pollution. The core objective was to develop an alternate approach to protecting productive farmland and populated areas by mitigating pollution in these susceptible zones. The NDVI and compactness index, along with their associated database, hold significant promise for environmental preservation efforts. This spatial procedure effectively maps the spatial temporal distribution of pollutants, providing targeted management strategies. The method's user-friendly nature makes it easily applicable in other African countries.